PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO PADA MATERI KARYA SENI RUPA DUA DIMENSI UNTUK SISWA KELAS X SMA NEGERI 1 PADANG - Fadhillah Fadhillah; Suib Awrus (Universitas Negeri Padang, 2021)
This study aims to develop practical and valid video-based learning media on two-dimensional art work material and to determine the validity, practicality, and effectiveness of video-based learning media on two-dimensional art work material. This type of research is development research. The 4D development model refers to Thiajaragan's theory (in Kurniawan, 2017: 14), namely define, design, develop, and disseminate. While the quality of the feasibility of the media in the study has been through the validity test of experts, teacher and student response questionnaires. The results showed that the video media developed for students in the two-dimensional art work of class X SMA met the valid criteria in terms of content / material, media, and language approaches, as well as the responses of teachers and students to video media were valid and practical, so it's ready to be tested on a large scale in class X SMA.Keywords: Learning Media, Video, and Two Dimensions.